Modelling micro-scale coalescence and transportprocesses in liquid aerosol filtration - Mead-Hunter, Ryan (Curtin University, 2012)
This work has examined the physico-chemical properties of coalescing filters on a micro-scale, considering them as either a capillary system or a fibre-droplet system. This work has developed a validated theoretical model for droplet-fibe forces in both phillic and phobic systems and a computational fluid dynamics solver for droplet-fibre systems. This work will significantly improve the design and optimisation of coalescing filter systems.